Effects of different water management strategies on critical nitrogen concentration dilution curves, nitrogen accumulation, and grain yield in winter wheat - Lu, Junsheng; Hu, Tiantian; Li, Yue; Cui, Xiaolu; Cheng, Minghui; Yan, Shicheng; Xiang, Youzhen; Fan, Junliang; Zhang, Fucang; Xiong, Youcai (Agriculture Communications, 2024)
The Nitrogen Nutrition Index (NNI), based on the Critical Nitrogen Concentration (Nc), is widely utilized to evaluate crop nitrogen nutrition. However, the impact of water deficit on crop Nc remains unclear. To address this, a 3-year joint water-nitrogen regulation experiment on winter wheat was conducted to investigate the responses of Nc dilution curve parameters (A1 and A2 in Nc ​= ​A1DM−A2, where DM represents aboveground dry biomass), nitrogen accumulation (NA), and grain yield (GY) to different water management strategies. The study employed Bayesian statistical methods to establish the Nc dilution curve, which revealed a slightly lower curve compared to that derived using classical methods. The posterior distribution indicated substantial overlap in parameters A1 (89.8%) and A2 (89.4%) between deficit irrigation (DI) and full irrigation (FI). The overlap of parameter A1 was 67.2% between rainfed and irrigated (DI and FI) treatments, whereas for parameter A2, it was only 29.9%. Analysis of variance showed a significant difference (p ​< ​0.05) in parameter A2 between rainfed and irrigated treatments, but no significant differences were found (p ​> ​0.05) between DI and FI treatments. Additionally, NA and GY of winter wheat displayed insignificant differences between irrigation treatments; however, they were, on overage, significantly higher by 31.2% and 23.2%, respectively, under irrigated conditions compared to rainfed conditions. This study is the first to demonstrate that severe water deficit (rainfed conditions) significantly affects parameter A2 of the Nc dilution curve, underscoring the importance of considering actual water conditions in applying the NNI for nitrogen fertilizer management.